Epidemiology of methicillin‐resistant Staphylococcus aureus in a Japanese neonatal intensive care unit. Issue 8 (3rd August 2020) - Tsujiwaki, Atsushi; Hisata, Ken; Tohyama, Yudai; Matsunaga, Nobuaki; Uehara, Yuki; Sasaki, Takashi; Hiramatsu, Keiichi; Shimizu, Toshiaki
Abstract: Background: There have been few reports on the genetic structure of the current population of methicillin‐resistant Staphylococcus aureus (MRSA) from neonatal intensive care units (NICUs) in Japan. In the present study we conducted a molecular epidemiological analysis based on whole genome sequencing against MRSA strains in a Japanese NICU. Methods: We performed genotyping by whole genome sequencing, polymerase chain reaction‐based typing of Staphylococcal cassette chromosome mec (SCC mec ) and polymerase chain reaction‐based open‐reading frame typing against 57 MRSA strains from fecal or nasal specimens from NICU patients in Juntendo University Shizuoka Hospital in 2013–2014. Results: Forty‐nine MRSA strains (86.0%) exhibited a clonal complex (CC) 1, and were divided into three sequence types (STs): ST2725 ( n = 25), ST2764 ( n = 21), and ST1 ( n = 3). All CC1 MRSA strains had SCC mec IVa, and were resistant to new quinolones, which are limited in pediatric use, suggesting that these strains were derived from adult MRSA clones. Single nucleotide polymorphism differences of both ≤10 and >100 nucleotides were observed by pairwise, single nucleotide polymorphism analysis among ST2725 and ST2764 MRSA strains, respectively. Seven ST8 MRSA strains (12.2%) were isolated, and no strain exhibiting the Japanese hospital‐associated MRSA genotype (ST5/SCC mec II) was isolated in this study. Conclusions: Our molecular epidemiological analysis suggested that ST2725 and ST2764 MRSA strains had genetic diversity that could not be explained only by a recent transmission event in the NICU. These MRSA clones might be disseminated in other Japanese hospital facilities as new endemic clones. Our results are expected to contribute to the improvement of infection control measures of MRSA in NICUs.